Class Size And Academic Performance Of Students In Selected Nursing And Midwifery Training Colleges In The Central Region, Ghana - Kusi, Hinneh; Manful, Hilda Obeng (Advances in Social Sciences Research Journal, 2019)
Large class size is a big challenge in most public tertiary educational institutions in Ghana. This study investigated the impact of class size on the academic performance of students of selected Nursing and Midwifery Training Colleges in the Central Region of Ghana, and determined the extent to which large class size management techniques employed by tutors enhance academic performance of the students. The study employed the mixed methods research approach underpinned by the pragmatist paradigm. Specifically, the sequential explanatory mixed methods design was used for the study. For the quantitative phase of the study, stratified and simple random sampling techniques were employed to select 131 students, while census sampling frame was employed to involve all the 56 tutors. Also, 20 participants made up of 10 tutors (who were Heads of Departments) and 10 student leaders were purposively selected for the qualitative phase. Two related structured questionnaire (1 for the students and the other for the tutors) were used to gather data for the quantitative phase, while a semi-structured interview guide was employed for data collection at the qualitative phase. Descriptive statistics (mean, standard deviation) and inferential statistics (one-way between groups analysis of variance (ANOVA), and multiple regression) were used to analyze the data so as to answer the research questions at a significance level of p <0.05. The one-way between groups ANOVA was used to determine the effect of class size on academic performance and large classroom management techniques. The data gathered through the semi-structured interview was also used to support the quantitative results when necessary. The study revealed that class size had an effect on the academic performance of the students where students in small class size recorded higher performance than their peers in large class sizes. The study, therefore, concluded that classroom size significantly influence academic performance of students at all levels. The relationship between classroom size and academic performance was found to be inversely related. Students in large classrooms performed poorly, while students in small classroom size performed better academically. To ensure a more meaningful academic performance among the students, small class sizes are needed to improve the interaction between tutors and students. Based on this finding, the study recommended that it is pertinent that the management of the colleges studied pay attention to the class sizes so as to ensure good academic performance.